Arterial Spin Labeling technique and clinical applications of the intracranial compartment in stroke and stroke mimics - A case-based review. Issue 4 (August 2022) - Daftari Besheli, Laleh; Ahmed, Amara; Hamam, Omar; Luna, Licia; Sun, Lisa R; Urrutia, Victor; Hillis, Argye E; Tekes-Brady, Aylin; Yedavalli, Vivek
Magnetic resonance imaging perfusion (MRP) techniques can improve the selection of acute ischemic stroke patients for treatment by estimating the salvageable area of decreased perfusion, that is, penumbra. Arterial spin labeling (ASL) is a noncontrast MRP technique that is used to assess cerebral blood flow without the use of intravenous gadolinium contrast. Thus, ASL is of particular interest in stroke imaging. This article will review clinical applications of ASL in stroke such as assessment of the core infarct and penumbra, localization of the vascular occlusion, and collateral status. Given the nonspecific symptoms that patients can present with, differentiating between stroke and a stroke mimic is a diagnostic dilemma. ASL not only helps in differentiating stroke from stroke mimic but also can be used to specify the exact mimic when used in conjunction with the symptomatology and structural imaging. In addition to a case-based overview of clinical applications of the ASL in stroke and stroke mimics in this article, the more commonly used ASL labeling techniques as well as emerging ASL techniques, future developments, and limitations will be reviewed.